Community Empowerment: Alderly Memory Stimulation with Rollmate to Postpone Cognitive Decrease - Julia Pertiwi; Arifatun Nisaa; Rika Andriani; Syefira Ayudia Johar (IJECS: Indonesian Journal of Empowerment and Community Services, 2026)
The increasing elderly population in Klaten Regency, reaching 17-18%, brings challenges in the form of an increased risk of cognitive decline and dementia. Posyandu (Integrated Health Post) Dahlia Mandiri in Tegal Malohan faces limitations in cognitive stimulation services due to a lack of media and the human resources capacity of its cadres. This community service activity aims to implement rollmate technology as a non-pharmacological intervention to improve the cognitive function of the elderly through the empowerment of Posyandu cadres. Training was conducted for six cadres using lecture and hands-on methods. The intervention was then applied to 55 elderly people over two cycles to measure the effectiveness of the tool's use on cognitive speed and scores. The cadre training showed a significant increase in knowledge, with an average pre-test score of 30.89 to 86.83 in the post-test. In the elderly group, the application of rollmate successfully increased the speed and duration of use by 1.5 minutes and increased scores by 100%. Qualitatively, elderly people reported feeling more "fresh" mentally and showed increased focus and stabilization of cognitive scores. The use of rollmate is effective as a means of stimulating eye-hand coordination and a recreational psychology for the elderly. Integrating this tool into routine posyandu activities is crucial for the sustainability of the intervention, with family support being a key factor in independent use at home. Keywords: Elderly, Cognitive Function, Rollmate, Posyandu Cadres